2017
DOI: 10.1186/s13104-017-2714-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of follow-up care associated with incident antidepressant use in older adults

Abstract: ObjectivesTo determine the proportion of older adults receiving guideline concordant antidepressant therapy and to determine patient, prescriber and organizational factors associated with adequate antidepressant therapy.MethodsThe study included secondary analyses of data collected in the Étude sur la Santé des Aînés (ESA) Services study on older adults recruited while consulting in primary care clinics in one of the largest health regions of the province of Québec. Antidepressant users (n = 349) were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Research has shown that over 50% of adult patients with depression or anxiety disorders do not receive guideline-concordant treatment [15][16][17][18]. Among older adults receiving antidepressant therapy, only 44% received an adequate dose and duration and had an appropriated number of physician follow-up visits [19].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that over 50% of adult patients with depression or anxiety disorders do not receive guideline-concordant treatment [15][16][17][18]. Among older adults receiving antidepressant therapy, only 44% received an adequate dose and duration and had an appropriated number of physician follow-up visits [19].…”
Section: Introductionmentioning
confidence: 99%
“…Houle et al [ 8 ] also found that people 65 years of age and older were less likely to receive follow-up care and to have high levels of continuity with their regular provider, but they did not assess the relationship between continuity and follow-up. Massamba et al [ 25 ] used survey data to assess follow-up care after a first antidepressant prescription in older adults in Quebec. They did not observe any differences in the Usual Provider of Care Index – a measure of continuity of care that calculates the proportion of visits performed by the provider that the patient visited most frequently – between older adults who received follow-up care and those who did not.…”
Section: Discussionmentioning
confidence: 99%